Peek-a-boo : factors that affect the activity level and behaviour of the red and white giant flying squirrels (Petaurista alborufus castaneus) in night safari. - Teo, Ni Zhen. (2012)
Red and White Giant Flying Squirrels are elusive animals that are hard to study, thus little is known about their behaviour both in the wild and in captivity. However, knowledge on behaviour is the most crucial for conservation efforts to succeed. Environmental factors that could affect the behaviour of 3 squirrels were observed and recorded over 60 days. The